Hubungan tingkat tekanan darah dengan stadium retinopati diabetik pada pasien di RSU Karsa Husada Kota Batu: Studi potong lintang - Nurrushodiq, Nahiza (Maliki Interdisciplinary Journal, 2026)
Diabetes mellitus is a chronic disease that requires long-term management due to its potential to cause various serious complications. One of the most common complications is diabetic retinopathy, a condition characterized by damage to the small blood vessels of the retina, which can impair vision and may ultimately lead to blindness. In addition to blood glucose levels, blood pressure is frequently identified as a factor that can worsen retinal vascular damage. Therefore, blood pressure control is considered an essential component of diabetes management. This study aimed to examine the association between blood pressure levels and the stage of diabetic retinopathy among patients with diabetes mellitus at Karsa Husada General Hospital, Batu City. An analytic observational study with a cross-sectional design was conducted. Data were obtained from patients’ medical records covering the period from 2020 to 2022. A total of 32 patients met the inclusion and exclusion criteria and were included in the analysis. Blood pressure was classified into normal, high-normal, stage 1 hypertension, and stage 2 hypertension. Diabetic retinopathy was categorized into non-proliferative diabetic retinopathy (NPDR) and proliferative diabetic retinopathy (PDR). Data analysis consisted of univariate analysis to describe patient characteristics and bivariate analysis using the Chi-square test. The results showed that most patients were classified as having stage 1 hypertension and were diagnosed with PDR. The Chi-square test yielded a p-value of 0.315, indicating no statistically significant association between blood pressure level and the stage of diabetic retinopathy. These findings suggest that the severity of diabetic retinopathy is influenced not only by blood pressure but also by other contributing factors. Consequently, diabetes management should be implemented comprehensively using a holistic approach.